2020
DOI: 10.3389/fimmu.2020.00406
|View full text |Cite
|
Sign up to set email alerts
|

Novel Lipidated Imidazoquinoline TLR7/8 Adjuvants Elicit Influenza-Specific Th1 Immune Responses and Protect Against Heterologous H3N2 Influenza Challenge in Mice

Abstract: Most licensed seasonal influenza vaccines are non-adjuvanted and rely primarily on vaccine-induced antibody titers for protection. As such, seasonal antigenic drift and suboptimal vaccine strain selection often results in reduced vaccine efficacy. Further, seasonal H3N2 influenza vaccines demonstrate poor efficacy compared to H1N1 and influenza type B vaccines. New vaccines, adjuvants, or delivery technologies that can induce broader or cross-seasonal protection against drifted influenza virus strains, likely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 81 publications
0
33
0
1
Order By: Relevance
“…Neonates were also protected against polymicrobial sepsis when infection was initiated 24 h after treatment ( 66 ). It is also important to note that imiquimod may be an effective vaccine adjuvant strategy for influenza ( 176 ).…”
Section: Toll-like Receptor Agonist-mediated Trained Immunity and Promentioning
confidence: 99%
“…Neonates were also protected against polymicrobial sepsis when infection was initiated 24 h after treatment ( 66 ). It is also important to note that imiquimod may be an effective vaccine adjuvant strategy for influenza ( 176 ).…”
Section: Toll-like Receptor Agonist-mediated Trained Immunity and Promentioning
confidence: 99%
“…Some polysaccharides from plants, bacteria, yeasts, and synthetic sources can simulate and activate innate cell types, and regulate adaptive immunity [ 34 ]. Importantly, polysaccharides that help create a Th1-type cellular response have been considered strong adjuvant candidates in the use of vaccines against cancer, viruses, and bacteria [ 35 , 36 , 37 ]. In the current study, we found that ALP could induce the phenotypic maturation of DCs by stimulating the expression of cell surface molecules, antigen-presenting ability, and Th1-polarizing pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Both cells were stably transfected with the secreted alkaline phosphatase (SEAP) reporter gene under the transcriptional control of an NF‐kB response element. The level of SEAP protein released into the culture media was used to quantify the extent of TLR7 stimulation, which also represents the levels of NF‐κB activation (Miller et al., 2020). HEK‐Blue‐Null1‐v and HEK‐Blue mTLR7 cells (1 × 10 4 ) were plated in 96‐well plates and grown to 70% confluence.…”
Section: Methodsmentioning
confidence: 99%